2015
DOI: 10.1177/230949901502300102
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Poor Platelet-Rich Plasma versus Bupivacaine for Recalcitrant Lateral Epicondylar Tendinopathy

Abstract: Purpose.To compare a single leukocyte-poor (type-4B) platelet-rich plasma (PRP) injection versus bupivacaine injection for recalcitrant lateral epicondylar tendinopathy (LET). Methods. 25 patients aged 27 to 50 years with painful and recalcitrant LET of the humerus were randomised to receive leukocyte-poor (type-4B) PRP (n=15) or bupivacaine (n=10) injection. Outcome measures included visual analogue scale (VAS) for pain, modified Mayo clinic performance index for elbow (MMCPIE) for elbow function, and Nirschl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 16 publications
2
66
0
Order By: Relevance
“…Mild complications, such as nausea and dizziness, which were of short duration, were observed in 6 patients (22.2%) in group I and 11 patients (44%) in group II. Tennis elbow study 13 : Improvement in the following functional scores (VAS for pain, mean MMCPIE score, and mean Nirschl score) was greater in the PRP group than in the bupivacaine group after 3 months (42. The difference in scores between groups was significant at 6 months and 1 year only (p < 0.001).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Mild complications, such as nausea and dizziness, which were of short duration, were observed in 6 patients (22.2%) in group I and 11 patients (44%) in group II. Tennis elbow study 13 : Improvement in the following functional scores (VAS for pain, mean MMCPIE score, and mean Nirschl score) was greater in the PRP group than in the bupivacaine group after 3 months (42. The difference in scores between groups was significant at 6 months and 1 year only (p < 0.001).…”
Section: Resultsmentioning
confidence: 97%
“…We have shown that the use of ultrasound for guided injections definitely helps in giving the injection at the right site, and this has also been advised by other authors. 13,29 However, the role of PRP in other tendinopathies like Achilles tendinopathy has not been encouraging, 30,31 despite successful usage of PRP in patellar tendinopathies. 32,33 Plantar fasciitis is also another commonly encountered problem which at times can be frustrating to both the patient and the treating doctor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The usage of platelet-rich plasma (PRP) has become relatively frequent, with well-selected indications, in cases that have failed all other physical therapy modalities plus a well-structured rehabilitation protocol. Our work on lateral epicondylitis, 32 compared a single injection of leukocyte-poor (type-4) with bupivacaine injections, and it has shown good improvement in pain and function for recalcitrant lateral epicondylitis. This has also been corroborated by other research ( Table 1 ), 32 -36 although larger multicentric studies are needed to recommend this as the best modality of management.…”
Section: Orthopedics and Sports Medicine Aspectsmentioning
confidence: 99%
“…However, in the CS group, the scores peaked at 3 months and then decreased, indicating recurrence of symptoms in 46.7% of the CS patients. Another study carried out by Behera et al [13] was a comparison of PRP injections versus bupivacaine injections for recalcitrant lateral epicondylar tendinopathy. The trial enrolled 25 patients whose condition was assessed with a VAS for pain, the modified Mayo clinic performance index for elbow (MMCPIE) and the Nirschl score for activity-related pain at 1, 3, 6 and 12 months.…”
Section: Use Of Platelet-rich Plasma In Enthesopathy and Tendinopathymentioning
confidence: 99%